Gender integration across the USAID feed the future innovation labs - Larson, Janelle (Pennsylvania State University, 2023)
Feed the Future Innovation Labs lead the research arm of the US Government’s initiative for food security, globally. Led by US universities and in collaboration with incountry researchers, these Innovation Labs are central to advancing novel solutions that support US goals to reduce global hunger, poverty and undernutrition, in both the natural and social sciences. This session will explore how various innovation labs incorporate gender across the research and implementation cycle to ensure solutions are gender transformative. The discussion will touch on collaboration with natural scientists; capacity strengthening in US and international research institutions as well as community partners; and policy and program development, all with an eye to transforming gender relations.